The implementation of augmented reality in geometry for primary school students / Hendra Pradibta, Odhitya Desta Triswidrananta and Maisia Rohmatul Jannah - Pradibta, Hendra; Triswidrananta, Odhitya Desta; Jannah, Maisia Rohmatul (UiTM Cawangan Perlis, 2023)
Mathematics is a subject studied from elementary education up to the university level. In general, learning mathematics uses a conventional approach using a whiteboard. This method has shortcomings in the process of visualization and simulation, especially in the material of geometry. This research develops a learning application by utilizing Augmented Reality technology with the content of geometry for sixth-grade primary school students. Augmented Reality can visualize and simulate geometry for students with an interaction model. Linear Congruential Generator (LCG) and Fuzzy Tsukamoto methods are used in this application as a randomization method and score determination method. The results obtained from the testing process show that the LCG and fuzzy Tsukamoto methods can run according to the design. In user testing using a questionnaire, the results obtained 4.6 of scale 5.0 indicating that respondents provided good responses for the Augmented Reality Geometry application.